The changing Spanish family essays on new views in literature, cinema and theater - Trotman, Tiffany Gagliardi (McFarland, 2011)
"Spain stands among Western countries that have recently embraced non-traditional families. Declining dominance of extended families, single-parent households, and increasing numbers of working mothers have transformed what it means to be a "Spanish family." This essay collection examines how authors, filmmakers and playwrights are exploring the cultural manifestations that come from the redefining of Spanish society"--Provided by publisher.